Role of institutions on the freedom of expression in the labor sphere: Critical analysis of the discourse on the jurisprudence of the Inter-American Court of Human Rights - González Aguilar, Hugo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This study aims to analyze the abuse of power exercised by institutions against the freedom of expression of workers in the labor context and the time it takes to resolve this problem. The methodology is qualitative, through content analysis of the rulings of the Inter-American Court of Human Rights on Peru and Venezuela. It is concluded that institutions abuse their power and violate freedom of expression and the right to work against the victims, who find justice after a long judicial process that lasts more than fifteen years.